Data Synergy between Altimetry and L-Band Passive Microwave Remote Sensing for the Retrieval of Sea Ice Parameters—A Theoretical Study of Methodology - Shiming Xu; Lu Zhou; Jiping Liu; Hui Lu; Bin Wang (Remote Sensing, 2017)
Accurate knowledge of the sea ice parameters, including the thickness and the snow depth over sea ice, are key to both climate change studies and operational forecast in polar regions. The estimation of these parameters mainly relies on satellite based remote sensing, and current retrieval algorithms usually focus on the retrieval of a single parameter under simple assumptions over the other. In this article, we explore the potential of combined retrieval of both sea ice thickness and snow depth through the data synergy two types of concurrent observations of the sea ice cover: the active altimetry and the L-band passive remote sensing. The data synergy is based on two physical constrains: (1) L-band (1.4 GHz) radiation model for the sea ice cover, and (2) the hydrostatic equilibrium as used in satellite altimetry. Two schemes of data synergy are proposed: (1) the synergy between L-band brightness temperature ( T B ) from passive microwave remote sensing and sea ice freeboard ( F B i c e ) as measured by radar altimetry, and (2) the synergy between L-band T B and snow freeboard ( F B s n o w ) as measured by laser altimetry. Based on retrievability studies, we show that both parameters can be retrieved using the two sets of data. Specifically, we show that there is potential problem of ill-posedness for the synergy between L-band T B and F B s n o w , with two possible retrieval solutions for a small portion of the solution space. On the other hand, the synergy between L-band T B and F B i c e is always well-posed. In terms of sensitivity, lower uncertainty is witnessed for thin ice for the retrieval with F B i c e , while the retrieval with F B s n o w shows advantage for thick ice. Besides the input parameters of T B , F B i c e and F B s n o w , the uncertainty associated with certain model parameters such as snow and ice densities is not negligible for the uncertainty estimation of the retrieved parameters. Verification is carried out with observational data from Operation IceBridge (OIB) campaigns and SMOS ...